Hubungan Sikap, Norma Subjektif, Persepsi Kontrol Perilaku, Kepedulian Lingkungan, dan Kesadaran Kesehatan terhadap Minat Beli Sirup Cascara Casandra Brand Netisane - Karimah, Bella Esla; Hapsari, Hepi; Saidah, Zumi; Wiyono, Sulistyodewi Nur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Caffeine sensitivity is one of the main obstacles to increasing coffee consumption. Casandra cascara syrup offers an innovative solution that is low in caffeine and high in antioxidants. Despite its significant health and environmental benefits, sales of this product are still fluctuating due to low consumer awareness and suboptimal marketing strategies. This study aims to analyze the variables that influence purchase intention of cascara casandra syrup using the Theory of Planned Behavior (TPB) approach. The variables studied include attitudes, subjective norms, perceived behavioral control, environmental concerns, and health awareness. This study uses a quantitative approach to the census method with data collected through questionnaires to consumers of cascara casandra syrup. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results showed that attitude, perceived behavioral control, environmental concern, and health awareness have a positive and significant relationship with purchase intention. In contrast, subjective norms have a negative and significant relationship, indicating that social pressure does not always encourage consumers to buy. Thus, this study contributes to the development of TPB by adding environmental concern and health awareness, and offers recommendations for improving marketing strategies through consumer education with an emphasis on added value.